Architectural modernity in El Salvador: the aesthetics of an ideal - Sofía Rivera (Realidad, 2017)
Modern architecture had a particular dynamics in each country of Latin America. In the case of El Salvador, it coincided with a significant increase in building sector from the 1940s to 1980s. It coincided also with the founding of new institutions related to construction such as Dirección de Urbanismo y Arquitectura (Direction of Urbanism and Architecture), Instituto de Vivienda Urbana (Institute of Urban Housing), Junta Nacional de Turismo (National Board of Tourism), among others. They promoted new tipologies of buildings such as movie theaters, scholar groups, market places and recreational centers. It is also noteworthy the arrival of new professionals in architecture, both of foreign origins or nationals trained abroad; the emergens of new spaces of thought and debate, such as de School of Architecture in the public university or the Grupo Salvadoreño de Arquitectos (Group of Salvadoran Architects); and it should also be underlined the new technical possibilities with the founding of enterprises that produced or distributed new materials such as lattice windows, corrugated sheets, or concrete blocks. Realidad: Revista de Ciencias Sociales y Humanidades No. 150, 2017: 9-39